Pyrolysis characteristic of coals with different metamorphic grades and its instruction to coalbed methane development. (2nd October 2017) - Xia, Peng; Li, Kunjie; Zeng, Fangui; Xiao, Xiong; Zhang, Jianliang; Xiang, Jianhua; Sun, Beilei
Abstract : Purpose: Pyrolysis for coal gas generation changes the composition, pore structure, permeability and adsorption capacity of coal. This work aims to discuss the utilization of coal pyrolysis on enhancing coalbed methane (CBM) production in the Gujiao area, Shanxi province, China. Design/methodology/approach: This research was conducted mainly by the methods of thermogravimetry mass spectrometry (TG-MS) analysis, liquid nitrogen adsorption experiment and methane isothermal adsorption measurement. Findings: The results can be concluded as that 400-700°C is the main temperature range for generating CH4 . Pore volume and specific surface area increase with increasing temperature; however, the proportion of micro pore, transition pore and macro pore has no difference. The optimum temperature for enhancing CBM production should be letter than 600°C because the sedimentation of tar and other products will occupy some pores and fissures after 600°C. Originality/value: Here in, to accurately recognize the suitable maximum temperature for heating development, a method enhancing CBM production, TG-MS, was adopted to analyze the products and the weight loss of coals with different ranks in the Gujiao area at temperature of 30-1, 100°C. And then the pore structure, porosity, permeability, methane adsorption capacity and thermal maturity of coals during pyrolysis were investigated with increased temperature from 30°C to 750°C. On these bases, the favorable condition for enhancing CBM production and the thermal evolution of coal were recognized.